A positive electrode material and preparation method, device and lithium ion battery

By double-layer coating on the surface of the high-nickel ternary active positive electrode material, uniform and thin coating is achieved by using gas-solid reaction, the problems of space charge layer and side reactions in sulfide solid batteries are solved, and the magnification and cycling performance are significantly improved.

CN119400845BActive Publication Date: 2025-03-25四川新能源汽车创新中心有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510000494.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-25
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

In sulfide solid state batteries, the difference in the concentration of lithium ion between the positive electrode material and the sulfide solid electrolyte causes the lithium ions to spontaneously move to the positive electrode side, forming a severe space charge layer, which in turn affects the rate performance. At the same time, high nickel and sulfide are prone to side reactions, and effective coating methods are needed to solve these problems.

Method used

High nickel ternary active material is used as the positive electrode material, and the lithium-rich coating and AlCl3 coating are successively coated on its surface to achieve a uniform and thin double-layer coating through gas-solid reaction.

Benefits of technology

Effectively eliminate space charge layer, improve rate performance and cycling performance, simple process, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400845B_ABST
    Figure CN119400845B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode material and a preparation method, device and lithium ion battery thereof, and relates to the technical field of battery materials. The positive electrode material comprises a high-nickel ternary active material and a first coating layer and a second coating layer sequentially coated on the surface of the high-nickel ternary active material; the material of the first coating layer comprises a lithium-rich coating, and the material of the second coating layer comprises AlCl3. The lithium-rich coating of the first coating layer of the present invention can effectively eliminate the space charge layer, and the second coating layer stabilizes the environmental adaptability of the material itself, with a simple process, environmental friendliness, and good rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode material and a preparation method and device thereof, and a lithium ion battery. Background Art

[0002] In order to obtain lithium batteries with higher energy density, sulfide solid-state batteries with high nickel ternary active materials as lithium carriers have received great attention. However, in sulfide solid-state batteries, due to the difference in lithium ion concentration between the positive electrode material and the sulfide solid electrolyte on the positive electrode side, lithium ions spontaneously move to the positive electrode side, forming a serious space charge layer. The existence of the charge layer leads to poor rate performance. At present, a high ion conductor electrolyte layer is generally coated on the positive electrode material side to alleviate the space charge layer. However, due to the limitations of existing coating methods and technical means, it is difficult to solve the problem of poor rate performance caused by the existence of the charge layer. At the same time, high nickel and sulfide solid electrolytes in sulfide solid-state batteries are prone to side reactions, and their surfaces also need to be coated.

[0003] Common coating methods include dry coating, wet coating, etc. Dry coating is difficult to form a uniform and thin coating layer. The wet process is more uniform than dry coating, but the coating is usually thicker, and it is difficult to form a uniform and thin coating. In addition, solution treatment of high nickel can easily lead to structural failure. Wet coating involves a large amount of waste liquid post-processing and is costly. At present, new coating methods such as fluidized bed coating and ALD coating technology are immature, costly, and cannot be scaled up for mass production. In view of this, the present invention provides a positive electrode material and a preparation method, device, and lithium-ion battery thereof. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a positive electrode material and a preparation method, device and lithium ion battery thereof, with the purpose of realizing a low-cost, uniform and thin coated high-nickel ternary active material.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] In a first aspect, a positive electrode material comprises a high-nickel ternary active material and a first coating layer and a second coating layer sequentially coated on the surface of the high-nickel ternary active material; the material of the first coating layer comprises a lithium-rich coating, and the material of the second coating layer comprises AlCl3 (aluminum chloride).

[0007] The beneficial effects of the present invention are:

[0008] (1) The high ion conductivity lithium-rich coating of the first coating layer of the present invention can effectively eliminate the space charge layer, and the second coating layer stabilizes the environmental adaptability of the material itself. The process is simple and environmentally friendly.

[0009] (2) The coating layer of the positive electrode material obtained by the present invention is uniform and thin, the space charge layer is small, and the rate performance and cycle performance are good.

[0010] Based on the above technical solution, the present invention can also be improved as follows.

[0011] Further, the lithium-rich coating includes Li2S (lithium sulfide);

[0012] And / or, the molecular formula of the high nickel ternary active material is LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y O2, where 0.8≤x<1, x+y<1.

[0013] The beneficial effects of adopting the above further scheme are: uniformly coating the lithium-rich coating with high ion conductivity and the second coating layer, eliminating the space charge layer, and improving the rate.

[0014] Furthermore, the average particle size of the high-nickel ternary active material is 2 μm to 15 μm;

[0015] And / or, the thickness of the first coating layer is 1 nm to 50 nm;

[0016] And / or, the thickness of the second coating layer is 1nm~10nm;

[0017] And / or, the first coating layer and the second coating layer coated on the surface of the high-nickel ternary active material are obtained in sequence through gas-solid reaction.

[0018] The beneficial effects of adopting the above further scheme are: creatively preparing uniformly coated and thin positive electrode materials through gas-solid reaction; the first coating layer provides high ion conductivity and eliminates the space charge layer, and the second coating layer covers the first coating layer, while protecting the positive electrode material from side reactions with the solid electrolyte.

[0019] In a second aspect, a method for preparing a positive electrode material comprises the following steps:

[0020] (1) sintering the high-nickel ternary active material under oxygen flow, so that the residual alkali lithium hydroxide and lithium carbonate on the surface of the high-nickel ternary active material are converted into Li2O (lithium oxide), thereby obtaining a sintered high-nickel ternary active material;

[0021] (2) heating the first coating to a temperature above the melting point to generate a first vaporized product, and allowing the first vaporized product to coat the surface of the sintered high-nickel ternary active material for the first time to obtain a high-nickel ternary active material having a first coating layer;

[0022] (3) The second coating is heated to above the melting point to generate a second vapor, and the second vapor is used to coat the surface of the high-nickel ternary active material having the first coating layer for a second time, thereby obtaining a high-nickel ternary active material having the first coating layer and the second coating layer, which is the positive electrode material.

[0023] The beneficial effects of adopting the above further scheme are:

[0024] (1) The present invention uses this method to achieve a uniform and thin double-layer coating on the surface of a high-nickel ternary active material by utilizing the pressure difference and the low melting point of the material. This method does not require complex and expensive equipment and technology, does not require large amounts of wastewater and waste gas treatment, has little environmental pollution, is low in cost, and is easy to promote on a large scale.

[0025] (2) The high ion conductivity lithium-rich coating of the first coating layer of the present invention can effectively eliminate the space charge layer, and the second coating layer stabilizes the environmental adaptability of the material itself, creatively preparing a uniformly coated and thin positive electrode material, with a simple process and environmental friendliness.

[0026] (3) The positive electrode material obtained by the above method has a uniform and thin coating layer, a small space charge layer, and good rate performance and cycle performance.

[0027] Furthermore, the sintering parameters in step (1) are: oxygen volume concentration ≥ 99%, temperature 300°C to 500°C, and time 2h to 10h. During sintering, rotation can be performed at a speed of 1rpm / min to 10rpm / min.

[0028] Furthermore, in step (2), the first coating comprises sulfur, and the first coating is preferably in powder form;

[0029] And / or, in step (3), the second coating comprises AlCl3.

[0030] Furthermore, the parameters of the first coating are: negative pressure of -50Pa~-400Pa, temperature of 110°C~150°C, and time of 1h~10h;

[0031] And / or, the parameters of the second coating are: negative pressure of -50Pa~-400Pa, temperature of 180°C~200°C, and time of 1h~10h.

[0032] Furthermore, the negative pressure in the first coating and the negative pressure in the second coating are both generated by temperature difference.

[0033] In the third aspect, a device, the preparation method used in the preparation device includes a first container A, a second container A and a container B; the first container A is connected to the container B through a first connecting valve, and the second container A is connected to the container B through a second connecting valve; the first container A is provided with a third air inlet, the second container A is provided with a fourth air inlet, the container B is provided with a first air inlet and a second air inlet, the container B is provided with a first air outlet and a second air outlet; the container B is provided with a feed port and a discharge port.

[0034] In a fourth aspect, a lithium-ion battery comprises the positive electrode material.

[0035] The beneficial effects of adopting the above scheme are: the lithium ion battery of the present invention adopts a positive electrode material with a uniform and thin coating layer, a small space charge layer, and good rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the device of the present invention;

[0037] Figure 2 Schematic diagram of the structure of the positive electrode material of the present invention.

[0038] In the accompanying drawings, the components represented by the reference numerals are listed as follows:

[0039] 1. First container A, 2. Second container A, 3. Container B, 4. First air inlet, 5. Second air inlet, 6. Third air inlet, 7. Fourth air inlet, 8. First air outlet, 9. Second air outlet, 10. First connecting valve, 11. Second connecting valve, 12. Feed inlet, 13. Feed outlet. DETAILED DESCRIPTION

[0040] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0041] This embodiment relates to a positive electrode material ( Figure 2 ), the positive electrode material includes a high-nickel ternary active material and a first coating layer and a second coating layer sequentially coated on the surface of the high-nickel ternary active material; the material of the first coating layer includes a lithium-rich coating, and the material of the second coating layer includes AlCl3.

[0042] In order to solve the space charge layer of solid-state batteries and improve the rate performance, the present invention utilizes the residual alkali on the surface of high-nickel ternary active materials, and can use the gas-solid reaction principle to adsorb the easily fusible and volatile coating material into the positive electrode material system, and use the gas-solid reaction to evenly coat the coating material on the surface of the high-nickel ternary active material, and further fully convert the residual alkali on the surface into a lithium-rich coating with high ionic conductivity; compared with liquids, at the microscopic level, the gas can better fully contact every corner of the solid surface. In order to prevent the high-ionic conductivity lithium-rich coating from reacting with other compounds or air, a more stable second coating layer is coated on its surface as a protective layer; at the same time, the problem of poor structural stability caused by the alternating expansion and contraction of the volume of the positive electrode active material during the lithium insertion and extraction process is avoided, and the structural stability is improved.

[0043] Therefore, the high ion conductivity lithium-rich coating of the first coating layer of the present invention can effectively eliminate the space charge layer, and the second coating layer stabilizes the environmental adaptability of the material itself. A uniformly coated and thin positive electrode material is creatively prepared through a gas-solid reaction. The process is simple, environmentally friendly, and has good rate performance and cycle performance.

[0044] In this embodiment, the lithium-rich coating with high ion conductivity includes Li2S;

[0045] And / or, the molecular formula of the high nickel ternary active material is LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y O2, where 0.8≤x<1, x+y<1.

[0046] In this embodiment, the average particle size of the high-nickel ternary active material is preferably 2 μm to 15 μm, such as 2 μm, 3 μm, 5 μm, 10 μm, 15 μm, etc.;

[0047] And / or, the thickness of the first coating layer is 1 nm to 50 nm; for example, 1 nm, 5 nm, 15 nm, 20 nm, 30 nm, 50 nm, etc.;

[0048] And / or, the thickness of the second coating layer is 1 nm to 10 nm; for example, 1 nm, 3 nm, 5 nm, 10 nm, etc.;

[0049] And / or, the first coating layer and the second coating layer coated on the surface of the high-nickel ternary active material are obtained in sequence through gas-solid reaction.

[0050] This embodiment also relates to a method for preparing a positive electrode material, comprising the following steps:

[0051] (1) sintering the high-nickel ternary active material under oxygen flow, so that the residual alkali lithium hydroxide and lithium carbonate on the surface of the high-nickel ternary active material are converted into Li2O, thereby obtaining a sintered high-nickel ternary active material;

[0052] (2) heating the first coating to above the melting point to generate a first vaporized product, wherein the first vaporized product is continuously in contact with the surface of the sintered high-nickel ternary active material, so that the first vaporized product coats the surface of the sintered high-nickel ternary active material for the first time, thereby obtaining a high-nickel ternary active material having a first coating layer;

[0053] (3) The second coating is heated to above the melting point to generate a second vapor, and the second vapor is continuously in contact with the surface of the high-nickel ternary active material having the first coating layer, so that the second vapor coats the surface of the high-nickel ternary active material having the first coating layer for a second time, thereby obtaining a high-nickel ternary active material having the first coating layer and the second coating layer, which is the positive electrode material.

[0054] The present invention uses the method to achieve a uniform and thin double-layer coating on the surface of a high-nickel ternary active material by utilizing the pressure difference and the low melting point of the material. The method does not require complex and expensive equipment and technology, does not require a large amount of wastewater and waste gas treatment, has low environmental pollution, low cost, and is easy to promote on a large scale. The high ion conductivity lithium-rich coating of the first coating layer of the present invention can effectively eliminate the space charge layer, and the second coating layer stabilizes the environmental adaptability of the material itself, creatively prepares a uniformly coated and thin positive electrode material, and the process is simple and environmentally friendly. The coating layer of the positive electrode material obtained by the present invention using the above method is uniform and thin, the space charge layer is small, and the rate performance and cycle performance are good.

[0055] In this embodiment, the sintering parameters in step (1) are: the volume concentration of oxygen is ≥99%, the temperature is 300°C~500°C, for example, 300°C, 400°C, 500°C, etc., and the time is 2h~10h, for example, 2h, 4h, 6h, 8h, 10h, etc.

[0056] In this embodiment, preferably, in step (2), the first coating material comprises sulfur, and the first coating material is preferably in powder form;

[0057] And / or, in step (3), the second coating material comprises AlCl3. During coating, the material is rotated / stirred, etc., and the rotation / stirring speed is 1 rpm / min to 10 rpm / min, for example, 1 rpm / min, 5 rpm / min, 10 rpm / min, etc.

[0058] Preferably, the parameters of the first coating are: negative pressure of -50Pa~-400Pa, such as -50Pa, -100Pa, -200Pa, -400Pa, etc., temperature of 110°C~150°C, such as 110°C, 140°C, 150°C, etc., time of 1h~10h, such as 1h, 2h, 4h, 6h, 8h, 10h, etc.;

[0059] And / or, the parameters of the second coating are: negative pressure of -50Pa~-400Pa, for example, -50Pa, -100Pa, -200Pa, -400Pa, etc., temperature of 180℃-200℃, for example, 180℃, 200℃, etc., time of 1h~10h, for example, 1h, 2h, 4h, 6h, 8h, 10h, etc.

[0060] Preferably, in this embodiment, the negative pressure in the first coating and the negative pressure in the second coating are both generated by temperature difference.

[0061] This embodiment also relates to a device ( Figure 1 ), the preparation method adopts a preparation device comprising a first container A1, a second container A2 and a container B3; the first container A1 is connected with the container B3 through a first connecting valve 10, and the second container A2 is connected with the container B3 through a second connecting valve 11; the first container A1 is provided with a third air inlet 6, the second container A2 is provided with a fourth air inlet 7, the container B3 is provided with a first air inlet 4 and a second air inlet 5, the container B3 is provided with a first air outlet 8 and a second air outlet 9; the container B3 is provided with a feed port 12 and a discharge port 13.

[0062] Using the above device ( Figure 1 ) Preparation of the positive electrode material of the present invention comprises the following specific steps:

[0063] Step 1: After the precursors and lithium salts are mixed evenly, oxygen is introduced, and the temperature is 650℃~900℃, such as 650℃, 700℃, 900℃, etc., and sintered for 5h~20h, such as 5h, 10h, 15h, 20h, etc. to prepare the positive electrode material. The precursor includes Ni x Co y Mn 1-x-y (OH)2 or Ni x Co y Al 1-x-y (OH)2, where 0.8≤x<1, x+y<1;

[0064] Step 2: Add the positive electrode material prepared in step 1 to container B3, start rotation, control the temperature to 300°C~500°C, for example, 300°C, 400°C, 500°C, etc., open the first air inlet valve and the first air outlet valve, introduce oxygen, sinter for 2h~10h, for example, 2h, 4h, 6h, 8h, 10h, etc., remove the residual alkali lithium hydroxide and lithium carbonate on the surface, generate Li2O, control the rotation speed to 1rpm / min~10rpm / min, for example, 1rpm / min, 5rpm / min, 10 rpm / min, etc., then introduce nitrogen to exclude oxygen, close the first air inlet valve and the first air outlet valve to seal container B3;

[0065] Step 3: Add the first coating material into the first container A1 and heat it to above the melting point, such as 150°C~400°C, for example, 150°C, 300°C, 400°C, etc. Open the first connecting valve 10, lower the temperature of the container B3, and use the negative pressure generated by the temperature drop of the container B3 to absorb the coating material volatilized in the first container A1 into the container B3 by using the negative pressure, and perform gas phase coating on the positive electrode material, control the temperature drop rate and negative pressure, and control the negative pressure to -50Pa~-400Pa, for example, -50 Pa, -100Pa, -200Pa, -400Pa, etc. Finally, control the coating temperature to 120°C, react for 1h~10h, for example, 1h, 2h, 4h, 6h, 8h, 10h, etc., to form the first coating layer.

[0066] Step 4: Add the second coating into the second container A2 and heat it to above the melting point, such as 150°C to 400°C, for example, 150°C, 300°C, 400°C, etc. After the reaction in step 3 is completed, the first connecting valve 10 is closed, the temperature of container B3 is raised to 300°C~500°C, for example, 300°C, 400°C, 500°C, etc., nitrogen is introduced to keep the pressure of the container system at a positive pressure, and then the air inlet valve is closed, and the second connecting valve 11 is opened to reduce the temperature of container B3. The negative pressure generated by the temperature drop of container B3 is used to absorb the coating volatilized in the second container A2 into container B3, and the positive electrode material is gas-phase coated. The temperature drop rate and negative pressure are controlled to control the negative pressure to -50Pa~-400Pa, for example, -50Pa, -100Pa, -200Pa, -400Pa, etc., and finally the coating temperature is controlled to 190°C, and the reaction is carried out for 1h~10h, for example, 1h, 2h, 4h, 6h, 8h, 10h, etc. to form a second coating layer.

[0067] Step 5: After the reaction is completed, open the third air inlet valve, the fourth air inlet valve and the second air exhaust valve, introduce dry nitrogen, and cool the temperature to below 80° C. to obtain the target positive electrode material.

[0068] This embodiment also relates to a lithium ion battery, which comprises the positive electrode material. The lithium ion battery of the present invention uses a positive electrode material with a uniform and thin coating layer, a small space charge layer, and good rate performance and cycle performance.

[0069] The following is a detailed description through examples and comparative examples.

[0070] Embodiment 1:

[0071] A method for preparing a positive electrode material in this embodiment includes the following steps:

[0072] The precursor Ni 0.9 Co 0.08 Mn 0.02 (OH)2 and lithium salt are weighed and mixed in a ratio of 1.03, and then sintered at 550℃ for 2h and 720℃ for 12h, with the heating rate and cooling rate controlled at 3℃ / min. When the temperature drops below 100℃, grind and sieve to obtain intermediate product A.

[0073] Add intermediate A into container B3, introduce oxygen, rotate at 2 rpm / min, heat to 500°C, keep warm for 2 hours to remove lithium hydroxide and lithium carbonate on the surface, then introduce nitrogen to remove oxygen, and then close the first air inlet valve and the first air outlet valve.

[0074] Add 1.0g of sulfur powder into the first container A1, close the third air inlet 6 and the first connecting valve 10, heat the first container A1 to 300°C, and open the first connecting valve 10 at the same time to reduce the temperature of the container B3. The air cooling rate is 3°C / min, and the negative pressure in the container B3 is controlled at -60Pa. Finally, the container B3 is controlled to be kept at 150°C for 5 hours to form a first coating layer.

[0075] Then, the first connecting valve 10 is closed, the temperature of container B3 is raised to 450°C, and at the same time, 0.5g of AlCl3 is added to the second container A2, the fourth air inlet 7 and the second connecting valve 11 are closed, the second container A2 is heated to 300°C, and then the second connecting valve 11 is opened to reduce the temperature of container B3, the air cooling rate is 3°C / min, and the negative pressure in container B3 is controlled at -60Pa, and finally, the container B3 is controlled to be kept at 150°C for 5h to form a second coating layer, thereby obtaining a thin and uniform coated positive electrode material.

[0076] Then, the third air inlet valve 3, the fourth air inlet valve 4 and the second air exhaust valve 2 were opened, and nitrogen was introduced to discharge the excess unreacted substances in the container. The temperature of the containers A and B dropped to 80° C. before the materials were discharged.

[0077] Comparative Example 1 (Fujiyaki):

[0078] A method for preparing a positive electrode material in this comparative example comprises the following steps:

[0079] The precursor Ni 0.9 Co 0.08 Mn 0.02 (OH)2 and lithium salt are weighed and mixed in a ratio of 1.03, and then sintered at 550°C for 2 hours and 720°C for 12 hours, wherein the heating rate and cooling rate are controlled at 3°C / min. When the temperature drops below 100°C, grind and sieve to obtain the product.

[0080] Comparative Example 2 (without adding sulfur powder):

[0081] A method for preparing a positive electrode material in this comparative example comprises the following steps:

[0082] Except that sulfur powder is not added to the first container A1, the other steps are the same as those in Example 1.

[0083] Comparative Example 3 (without adding AlCl3):

[0084] A method for preparing a positive electrode material in this comparative example comprises the following steps:

[0085] Except that AlCl3 is not added to the second container A2, the other steps are the same as those in Example 1.

[0086] Comparative Example 4:

[0087] A method for preparing a positive electrode material in this comparative example comprises the following steps:

[0088] The precursor Ni 0.9 Co 0.08 Mn 0.02 (OH)2 and lithium salt were weighed and mixed in a ratio of 1.03, and then sintered at 550℃ for 2h and 720℃ for 12h, wherein the heating rate and cooling rate were controlled at 3℃ / min. When the temperature dropped below 100℃, the intermediate product A was obtained by grinding and sieving.

[0089] Add intermediate product A into container B3, introduce oxygen, rotate at 2 rpm / min, heat to 500°C, keep warm for 2 hours to remove lithium hydroxide and lithium carbonate on the surface, then introduce nitrogen to remove oxygen, and obtain intermediate product B;

[0090] After mixing the intermediate product B with the same sulfur powder as in Example 1 at high speed, add it into container B3 and keep it at 150°C for 5 hours.

[0091] Comparative Example 5:

[0092] A method for preparing a positive electrode material in this comparative example comprises the following steps:

[0093] The steps are the same as those in Example 4, except that the intermediate B is mixed with the same sulfur powder and AlCl3 as in Example 1 and then added to container B3 and kept at 150°C for 5 hours.

[0094] Test example

[0095] The positive electrode material, sulfide solid electrolyte (LSPC), and conductive agent (SuperC) prepared in Example 1 and Comparative Examples 1 to 5 were weighed in a mass ratio of 60:40:5, ground and mixed evenly, and pressed into tablets in a mold battery. Lithium indium was used for the negative electrode, and the preparation pressure was 2.5T.

[0096] (1) Cycle test

[0097] After the mold battery was placed for 10 hours, it was placed on a blue battery tester (CT2001C) for charge and discharge cycling.

[0098] (2) Performance testing

[0099] The test conditions are set as follows: 45°C, 2.7~4.3V (VsLi / Li+), 1C=200mAh·g -1 , 0.05C / 0.05C half-cell test for 1 cycle, and 1C / 1C cycle for 100 cycles to investigate the specific capacity and cycle performance of the positive electrode material. The specific electrochemical performance is shown in Table 1 below.

[0100] Table 1

[0101]

[0102] In summary, the present invention utilizes the residual alkali on the surface of the high-nickel ternary active material itself, and utilizes the gas-solid reaction principle to adsorb the easily fusible and volatile coating material into the positive electrode material system, and utilizes the gas-solid reaction to evenly coat the coating material on the surface of the high-nickel ternary active material, and further fully converts the residual alkali on the surface into a lithium-rich coating with high ionic conductivity; compared with liquids, at the microscopic level, the gas can better fully contact every nook and cranny of the solid surface. In order to prevent the high-ionic conductivity lithium-rich coating from reacting with other compounds or air, a more stable coating protective layer is coated on its surface; at the same time, the problem of poor structural stability caused by the alternating expansion and contraction of the volume of the positive electrode active material during the lithium insertion and extraction process is avoided, thereby improving the structural stability.

[0103] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes a high-nickel ternary active material and a first coating layer and a second coating layer sequentially coated on the surface of the high-nickel ternary active material; the material of the first coating layer includes a lithium-rich coating, and the material of the second coating layer includes AlCl3; The lithium-rich coating includes Li2S; And / or, the molecular formula of the high nickel ternary active material is LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y O2, where 0.8≤x<1, x+y<1; The first coating layer and the second coating layer coated on the surface of the high-nickel ternary active material are obtained in sequence through gas-solid reaction.

2. A positive electrode material according to claim 1, characterized in that: The average particle size of the high-nickel ternary active material is 2 μm to 15 μm; And / or, the thickness of the first coating layer is 1 nm to 50 nm; And / or, the thickness of the second coating layer is 1 nm to 10 nm.

3. A method for preparing a positive electrode material according to any one of claims 1 to 2, characterized in that: The steps include: (1) sintering the high-nickel ternary active material under oxygen flow, so that the lithium hydroxide and lithium carbonate on the surface of the high-nickel ternary active material are converted into Li2O, thereby obtaining a sintered high-nickel ternary active material; (2) heating the first coating to above the melting point to generate a first vaporized product, and then using the first vaporized product to perform a first coating on the surface of the sintered high-nickel ternary active material to obtain a high-nickel ternary active material having a first coating layer; (3) The second coating is heated to above the melting point to generate a second vapor, and the second vapor is used to coat the surface of the high-nickel ternary active material having the first coating layer for a second time, thereby obtaining a high-nickel ternary active material having the first coating layer and the second coating layer, which is the positive electrode material.

4. The preparation method according to claim 3, characterized in that: The sintering parameters in step (1) are: oxygen volume concentration ≥ 99%, temperature 300°C ~ 500°C, and time 2h ~ 10h.

5. The preparation method according to claim 3, characterized in that: In step (2), the first coating material comprises sulfur; And / or, in step (3), the second coating comprises AlCl3.

6. The preparation method according to claim 3, characterized in that: The parameters of the first coating are: negative pressure of -50Pa~-400Pa, temperature of 110℃~150℃, and time of 1h~10h; And / or, the parameters of the second coating are: negative pressure of -50Pa~-400Pa, temperature of 180°C~200°C, and time of 1h~10h.

7. The preparation method according to claim 6, characterized in that: The negative pressure in the first coating and the negative pressure in the second coating are both generated by temperature difference.

8. A device, characterized in that: The preparation device used in the preparation method described in any one of claims 3 to 7 includes a first container A, a second container A and a container B; the first container A is connected to the container B through a first connecting valve, and the second container A is connected to the container B through a second connecting valve; the first container A is provided with a third air inlet, the second container A is provided with a fourth air inlet, the container B is provided with a first air inlet and a second air inlet, and the container B is provided with a first air outlet and a second air outlet.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and secondary battery

    CN117577848A

  • Positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device

    CN119208586A